Expert reviewHypoplastic left heart syndrome – a review of supportive percutaneous treatment - Moszura, Tomasz; Góreczny, Sebastian; Dryżek, Paweł (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
Due to the complex anatomical and haemodynamic consequences of hypoplastic left heart syndrome (HLHS), patients with the condition require multistage surgical and supportive interventional treatment. Percutaneous interventions may be required between each stage of surgical palliation, sometimes simultaneously with surgery as hybrid interventions, or after completion of multistage treatment. Recent advances in the field of interventional cardiology, including new devices and techniques, have significantly contributed to improving results of multistage HLHS palliation. Knowledge of the potential interventional options as well as the limitation of percutaneous interventions will enable the creation of safe and effective treatment protocols in this highly challenging group of patients. In this comprehensive review we discuss the types, goals, and potential complications of transcatheter interventions in patients with HLHS.